2017
DOI: 10.1353/jmm.2017.0015
|View full text |Cite
|
Sign up to set email alerts
|

Millennials and the Future of Magazines: How the Generation of Digital Natives Will Determine Whether Print Magazines Survive

Abstract: I am pleased to have this opportunity to thank the many colleagues, friends, and faculty members who have helped me with this research project. I am most indebted to Chris Roberts, the chairman of this thesis, for sharing his research expertise and wisdom in connection with this project. I am so appreciative of his constant willingness to offer helpful answers and advice for my steady flow of inquiries throughout this process. I am also very grateful to Dianne Bragg, the co-chair of this thesis, for her contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Indeed, in their study of millennials aged 18 to 25 years old, Bonner and Roberts (2017) found that participants derived more enjoyment from a print magazine's physical attributes, including factors such as the scent of paper, which outweighed the convenience of online content. Also, Thurman and Fletcher (2019) found that when the UK magazine New Musical Express (NME) became an online-only publication, the title's reach unsurprisingly improved, but engagement decreased.…”
Section: Organisational Structuresmentioning
confidence: 99%
“…Indeed, in their study of millennials aged 18 to 25 years old, Bonner and Roberts (2017) found that participants derived more enjoyment from a print magazine's physical attributes, including factors such as the scent of paper, which outweighed the convenience of online content. Also, Thurman and Fletcher (2019) found that when the UK magazine New Musical Express (NME) became an online-only publication, the title's reach unsurprisingly improved, but engagement decreased.…”
Section: Organisational Structuresmentioning
confidence: 99%